Ultrasonographic characterization of cervical lymph nodes in healthy dogs. Issue 5 (16th July 2019) - Ruppel, Marissa J.; Pollard, Rachel E.; Willcox, Jennifer L.
Abstract: Ultrasonography provides a minimally invasive method to evaluate the cervical lymph nodes in dogs as part of staging head and neck cancer; however, standardized cohesive reports of the normal lymph node size and appearance are lacking. The purpose of this prospective, descriptive, reference interval study was to characterize the ultrasonographic appearance of cervical lymph nodes in 27 clinically healthy dogs. The size, shape, echogenicity, and margination of the mandibular, medial retropharyngeal, and superficial cervical lymph nodes were evaluated and correlated with age, breed, sex, body weight, and stage of dental disease. The appearance of the lymph nodes was variable among the population. The majority were cigar or ovoid in shape with smooth margins. The echogenicity of the mandibular lymph nodes was predominantly hypoechoic whereas the medial retropharyngeal lymph nodes were predominantly isoechoic compared to the salivary glands. The superficial cervical lymph nodes were predominantly hyperechoic to the surrounding muscle bellies. Higher body weight and younger age were associated with increased size in the medial retropharyngeal and superficial cervical lymph nodes ( P ‐values < .05). Sex and breed were not found to correlate with lymph node characteristics, and there was no trend noted in lymph node appearance associated with dental disease. These data establish normal parameters for the ultrasonographic size and appearance of cervical lymph nodes in dogs and can provide a reference of comparison for future canine cervical ultrasounds, which can be considered for routine staging procedures for head and neck cancer.